(untitled) (Journal of Hama University, 2020)
It used (18) Shami goat kids in center of scientific agriculture research in Hama, Kids were (150) days old, weighting in average (23.2)kg, Kids were divided into 3 groups depending on protein source of their feeding (non de-Hulled cottonseed meal 100% in group1, Soybean meal 100% in group2, and non de-Hulled cottonseed meal 50% and Soybean meal 50% in group3), blood samples were collected from experiment Kids to study before feeding by this diets ( as control ), and post 1,2,3 months from start feeding. For studying (LDL cholesterol, HDL cholesterol, Total cholesterol, Threeglycered Tg and AST ) in blood to evaluation Kids health case after feeding on this diets. Results showed Low significant (P≤0.05) in LDL cholesterol in 1,2,3 months after feeding in all groups, and Low significant (P≤ 0.05) in HDL cholesterol in 1,2 months after feeding in groups 1 and higher significant (P≤ 0.05) in 1,2,3 months after feeding in groups 2, but higher significant (P≤0.05) in Tg in 1,2 month after feeding in groups 1,and (P≤ 0.001) after three months from feeding in all groups, There were not found any significant changes in T. cholesterol, and AST in all groups. The study concluded feeding Shami goat Kids on diets contents on non de-Hulled cottonseed meal 100% or Soybean meal 100% acceptable results in growth and good health case after feeding for three months on this diets while the used diet contents non de-Hulled cottonseed meal 50% and Soybean meal 50% give a good efficiency metabolic and doesn’t show non undesirable changes in healthy case.